Social impact bond feasibility study of "DRIVE" intervention to address domestic violence in Germany - Farokhfar, Felix (2021)
Domestic violence is one of the most pressing social problems on a global scale. In Germany alone, the number of domestic violence cases reached an all-time high in 2019 with a recorded 141,792 offences, of which 140 turned out to be fatal. Despite the state's efforts to combat the problem, the numbers are still on the rise, which is largely attributed to the inadequacy of the current intervention models. One model, however, which showed promising results is called DRIVE, a U.K. based intervention that focus on high-harm, high-risk and/or serial perpetrators to reduce the recidivism rate by 30%. The aim of the present thesis is to assess whether a Social Impact Bond (SIB), an innovative outcome-based financing mechanism, is a suitable way of financing the intervention by replicating the model as a pilot in Berlin, Germany. For this purpose, a financial model was built in Microsoft Excel to compute the internal rate of return (IRR), as well to outline potential savings for the government.